A revision of the South African riffle beetle genus Leielmis Delève, 1964 (Coleoptera: Elmidae) - Bilton, David T. (Zootaxa, 2017)
The riffle beetle genus Leielmis Delève, 1964 is redescribed and shown to contain three species, all of which are apparently endemic to the South African Cape, where they live in permanent mountain streams with cold running water. A lectotype is designated for Helmis georyssoides Grouvelle, 1890, and two additional species (L. gibbosus sp. nov. and L. hirsutus sp. nov.) are described for the first time. Following study of the type series, L. georyssoides is shown to be endemic to Table Mountain; most specimens previously assigned to this taxon representing an additional species (L. gibbosus sp. nov.), widespread in the interior Cape Fold Mountains. The record of Leielmis from Angola is considered highly doubtful. Comparative notes and a key are provided to allow the identification of known species of the genus.